2019
DOI: 10.1177/0284185119852729
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer reproducibility of quantitative dynamic susceptibility contrast and diffusion MRI parameters in histogram analysis of gliomas

Abstract: Background Dynamic-susceptibility contrast and diffusion-weighted imaging are promising techniques in diagnosing glioma grade. Purpose To compare the inter-observer reproducibility of multiple dynamic-susceptibility contrast and diffusion-weighted imaging parameters and to assess their potential in differentiating low- and high-grade gliomas. Material and Methods Thirty patients (16 men; mean age = 40.6 years) with low-grade (n = 13) and high-grade (n = 17) gliomas and known pathology, scanned with dynamic-sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In another study, Dijkstra et al . showed that freeform ROIs that encompassed the whole tumour had a good diagnostic accuracy in differentiating low grade from high grade tumour [ 29 ]. In accordance with these results, we suggest that exclusion of the necrotic centre could be skipped from routine post-processing without preventing the distinction between pseudoprogression and tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Dijkstra et al . showed that freeform ROIs that encompassed the whole tumour had a good diagnostic accuracy in differentiating low grade from high grade tumour [ 29 ]. In accordance with these results, we suggest that exclusion of the necrotic centre could be skipped from routine post-processing without preventing the distinction between pseudoprogression and tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its operator dependency and inter-observer variability, this is the most widely used method in clinical practice. 9 , 10 , 11 , 12 …”
mentioning
confidence: 99%
“…Dijkstra et al proved that out of all the parameters to compare on MRI, rCBV was the most reproducible between observers (other parameters included apparent diffusion coefficient, maximum contrast enhancement, time to peak, wash in rate, and wash out rate) (7). They also determined that single slice ROI selection is not significantly different from attempting to capture the whole tumor in a 3D; thus, 2D selection is sufficient.…”
mentioning
confidence: 99%